Endogenous Galectin-1 in T Lymphocytes Regulates Anti-prostate Cancer Immunity - Corapi, Enrique; Carrizo, Gustavo; Compagno, Daniel; Laderach, Diego (Frontiers in Immunology, 2018)
The identification of effective new therapies for prostate cancer (PCa) requires a better understanding of the multiple molecular interactions between tumor cells and their associated microenvironment. In this context, galectin-1 (Gal-1) is a key molecule in the determination of the prostatic carcinoma microenviroment; therefore, it is essential to understand all the molecular processes in which this protein is involved. Most of the previous studies found in the literature have focused on the microenvironment remodeling properties of tumor-secreted Gal-1, through its interactions with the glyco-receptors at the cell membrane and the extracellular matrix. This report shows original aspects of the lectin by focusing on the role of lymphocyte endogenous Gal-1 in controlling anti-prostate tumor immunity. Using a murine preclinical model of prostate cancer, our results demonstrate that endogenous Gal-1 in lymphocytes modulates their proliferative rate and cytotoxic function in conditions of high extracellular Gal-1 concentration, mainly derived from tumor cells. In such conditions, the absence of Gal-1 in T lymphocytes potentiates anti-tumor immune responses. Further studies demonstrated that endogenous Gal-1 in CD4+, but mainly in CD8+T cells, acts as a negative regulator of anti-tumor immunity. In conclusion, prostate tumors require Gal-1 in lymphocytes to evade immune responses. This report lays the foundation for an original immunotherapy strategy for prostate cancer.